Intercultural Competence-Based Cultural Values in English Language Teaching at An Islamic Boarding School in Indonesia - Soni Ariawan (International Journal of English and Applied Linguistics (IJEAL), 2024)
The present research aims to explore English teachers’ perception of intercultural competence in English language teaching at one of the Islamic schools in Lombok, Indonesia. Cultural categories and aspects were analyzed using Cortazzi and Jin’s category of culture and Byram’s checklist of cultural aspects. This qualitative case study employed observation, textbook analysis, and interviews to gain the primary data. Three English teachers were involved in an in-depth interview. The findings revealed that the teachers positively perceive intercultural competence in ELT. Furthermore, local culture was still dominant in the textbook and the teachers confirmed that local culture exposure was pivotal for students as they might be able to introduce the cultural content or products to foreigners. In terms of cultural aspects, the teachers recommended food and historical or famous places that should be recognized by the students to enhance intercultural competence. It is suggested that English teachers should introduce cross-cultural values toward intercultural competence to the students.